Mainstreaming Empowerment in the Bolivia PRSP Monitoring and Evaluation at the Municipal Level - John-Abraham, Indu; Torres, Magüi Moreno (World Bank, Washington, DC, 2012)
Since the early 1990s, the Bolivian government has begun a transition towards a more decentralized form of government. As a result, the country's 324 municipalities have greater autonomy and responsibilities and several social control mechanisms have been created to promote more participation in local government and more accountability. In this context, the Bolivian government developed a Poverty Reduction Strategy Paper (PRSP) in May 2001, which is being revised in 2003. The PRSP outlines an approach to increased poverty related spending through investments in education, health and sanitation, and risk management. These expenditures will be planned and executed largely at the municipal level. The Popular Participation Law of 1994 established municipal oversight committees (comit?s de vigilancia) to help evaluate the impact of public policies and spending. However, without municipal information systems, the oversight committees and local governments lack the tools and resources necessary to fulfill their monitoring responsibilities.